Transcatheter closure of very large secundum atrial septal defects: long-term follow-up study. (12th October 2011) - Hong, Wu; Jing, Liu; Xianxian, Zhao; Bo, Liu; Yanyan, Wang; Xing, Zhen; Jing, Sun; Jingwei, Pan; Fuzhi, Guo; Weiping, Li; Ersong, Wang; Yongwen, Qin
Abstract : Aims: To evaluate the efficacy and safety of transcatheter closure of very large secundum atrial septal defects (ASD) with long-term follow-up results. Methods and results: From June, 2001 to June, 2008, 74 patients diagnosed as secundum atrial septal defect with a diameter more than 30 mm were enrolled in the study. Percutaneous closure of ASDs were attempted by using the Domestic Shanghai ASD-O guided by transthoracic echocardiography (TTE). For the group of the 74 patients, 68 of them are adults. The closure was successful in 71/74 patients (96%). The mean diameter of the device was 38.2±2.73 mm. During the follow-up, complete closure could be achieved in 100% of patients. 7 adverse events (9.9%) were reported. Most adverse events were categorised as minor and there was one major adverse events (1.4%). Conclusion: Transcatheter device closure is an effective management option for patients with very large ASD. Serious complications were rare.